EVALUASI KUALITAS GAMBAR RADIOGRAFI TORAKS DI RSI SITI RAHMAH PADANG - Vina Tri Septiana; Mita Febrianti; Sri Wahyuni (Yayasan Nusantara Hasana Berdikari, 2026)
Chest radiograph is said to have high quality if radiograph has all the information needed in establishing the diagnosis. If the quality of the image decreases, it is possible for the diagnosis given to the patient to be less accurate. Based on the opinion of radiologists, there are five criteria for assessment of chest radiograph; anatomical and image coverage, symmetrical, insufficient inspiration, adequate penetration, and scapula outside the lung area. This study aims to evaluate the quality of chest radiographs at Siti Rahmah Hospital in 2019. This research was conducted from October to December 2019 in the Radiology Installation section of Siti Rahmah Hospital, Padang. Chest radiographes were collected from January to April in 2019 recorded at the Radiology Installation of Siti Rahmah Hospital in Padang total 100 samples. The results showed that about 40 people (40,0%) of chest radiograph met all the image criteria but the remaining 60 people (60,0%) did not meet these criteria because they did not meet the anatomical and image coverage (2,0%), asymmetric (23,0%), inadequate penetration (11,0%), and scapula out of the lung fields (50,0%).